Peculiarities of aggressive behavior manifestation and mental self-regulation in police officers during the war - Vorobiova, Olha V.; Воробйова, Ольга Володимирівна; Воробйова, О. В.; Shylina, Alla A.; Шиліна, Алла Андріївна; Шиліна, А. А.; Ponomarenko, Yana S.; Пономаренко, Яна Сергіївна; Пономаренко, Я. С.; Hresa, Nataliia V.; Греса, Наталія Володимірівна; Греса, Н. В.; et al. (Warsaw : «Aluna Publishing», 2025)
Aim: To compare the peculiarities of aggressive behavior and mental self-regulation in police officers with different experiences of service activities in the conditions of war. Materials and Methods: The research was conducted during 2023-2024 among police officers (n = 68) and the 3rd training year police cadets (n = 72). Research methods: analysis and generalization of literary sources, psycho-diagnostic methods, methods of mathematical statistics. Results: Differences in the manifestations of aggression between police officers and cadets were found. In particular, the cadets demonstrated significantl (p < 0.001) higher values on the scales of “Suspicion” (4.2 points) and “Hostility index” (7.4 points), which indicates a more pronounced tendency to interpret the social environment as potentially threatening. At the same time, police officers showed significantly (p < 0.001) higher indicators on the scales of “Physical aggression” (8.2 points) and “Aggression index” (22.6 points), which indicates a readiness to physically respond to a threat. It was found that police officers have a significantly lower level of general mental self-regulation (24.0 points) and flexibility (6.3 points) compared to cadets (32.7 and 7.0 points, respectively), which may indicate the rigidity of behavioral strategies due to adaptation to professional activities under martial law. Conclusions: The results obtained indicate the need to develop mechanisms of self-regulation in police officers as a critical component of the system of psychological support for the professional activities of police officers, prevention of their aggressive behavior, especially in the context of performing service duties in situations of increased threat and uncertainty characteristic of wartime.
Vorobiova O. V. Peculiarities of aggressive behavior manifestation and mental self-regulation in police officers during the war / O. V. Vorobiova, A. A. Shylina, Y. S. Ponomarenko et al. // Wiadomosci lekarskie (Warsaw, Poland : 1960). – Warsaw : «Aluna Publishing», 2025. – 78(8). - P. 1530-1537. URL: https://doi.org/10.36740/WLek/209505
Keywords: self-regulation; aggression; police activities; locus of control